Desain E-Arsip Surat berbasis Web di Kantor Desa Kedungwaringin Bekasi - Bisri, Muawan; Andriati, Dea Andini (SAINTEKBU, 2021)
This study aims to design a letter archive application at the Kedungwaringin Village Office. The data collection method used is by conducting observations, interviews, literature studies and documentation that relates to the problem being studied. Based on the results of observations and observations made, the problem that hinders the process of filing mail archives is because it is still done manually so it is less effective and efficient in its implementation. The suggestions are given to improve the mail archive system that has been running, namely by replacing the manual system by building computer applications so that the mail archive management process is more effective and efficient, faster in making mail archive reports, making it easier to store and search for archived mail data. The results of this study are the design of e-archive applications that can be built using the PHP programming language and MySQL database as the database and the application development method used by using the waterfall method.